2018
DOI: 10.1093/jas/sky023
|View full text |Cite
|
Sign up to set email alerts
|

Responses in the rumen microbiome of Bos taurus and indicus steers fed a low-quality rice straw diet and supplemented protein

Abstract: Bos indicus typically perform better than Bos taurus when consuming a low-quality diet; however, the response to supplementation is generally greater in B. taurus. The underlying mechanisms supporting these responses have not been fully elucidated. Characterization of differences in rumen prokaryotic populations and their functional role in the two subspecies may provide additional insight. Ten cannulated steers (5 Angus and 5 Brahman) were used in concurrent 5 × 5 Latin squares. Animals were offered ad libitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 44 publications
4
13
0
Order By: Relevance
“…Therefore, our findings support both the suitability of our pro- (Henderson et al, 2015). For example, Prevotellaceae and Ruminococcaceae were found to be abundant in cattle fed a highly fibrous diet (Latham et al, 2018).…”
Section: Bacterial Communitiessupporting
confidence: 81%
“…Therefore, our findings support both the suitability of our pro- (Henderson et al, 2015). For example, Prevotellaceae and Ruminococcaceae were found to be abundant in cattle fed a highly fibrous diet (Latham et al, 2018).…”
Section: Bacterial Communitiessupporting
confidence: 81%
“…According to prior analyses (Chen et al, 2008; Latham et al, 2018), low-quality diets in low protein supplementation had greater bacterial diversity, which could be interpreted as a further feature of the diet that contains more secondary plant compounds in low-quality diets compared to high-quality diets. (Belanche et al, 2012; Fernandes et al, 2014) also reported that a fiber-based diet promotes higher levels of dietary microbial diversity since fiber fermentation produces more by-products compared to starch fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…Among genera detected in milk samples, many belong to phyla and genera known to belong to the core microbiome of the bovine rumen, like Prevotella , Butyrivibrio , Ruminococcus , Lachnospira , and Clostridium [50, 51]. Their presence in the milk samples is not surprising as bacteria from the rumen also end up in faeces and on external body sites and the environment of the cow.…”
Section: Discussionmentioning
confidence: 99%